Ukrainian refugees' return intentions and integration in the course of time - Joop Adema; Cevat Giray Aksoy; Yvonne Giesing; Panu Poutvaara (EconPol Forum, 2024)
Most Ukrainians plan to return, but the share of Ukrainian refugees planning to settle outside of Ukraine has gradually increased and reached 25 percent by mid-2024.By June 2024, 12 percent of Ukrainian refugees had returned to Ukraine and 7 percent had moved to another host country compared to 2022. Liberation of certain districts in late 2022 increased the probability of people from there returning to Ukraine by 5 percentage points. Local conflict in home municipality has redirected return to other parts of Ukraine, without reducing the overall probability of returning. The EU should encourage Ukrainian refugees to return once the conflict is over, but also help them to find work while under temporary protection.
Keywords: 330